Effect of curcumin on gene expression and protein level of methionine sulfoxide reductase A (MSRA), SOD, CAT and GPx in Freund’s adjuvant inflammation-induced male rats - Meshkibaf MH; Maleknia M; Noroozi S (Journal of Inflammation Research, 2019)
MH Meshkibaf, M Maleknia, S Noroozi Department of Clinical Biochemistry, Fasa University of Medical Sciences, Fasa, IranCorrespondence: M MalekniaDepartment of Clinical Biochemistry, Fasa University of Medical Sciences, Fasa, IranTel +98 933 437 7956Email maleknia.m2014@gmail.comObjective: Curcumin is the well-known compound which is extracted from turmeric powder, the dried rhizome of the Curcuma longa Linn. This have been used for the treatment of various disorders including inflammation. In this study we have analyzed the effect of curcumin on arthritis induced by adjuvant in rats, considering changes in methionine sulfoxide reductase A (MSRA) expression and antioxidant enzymes levels.Methods: Five groups of adult male Wistar rats (n=10), were randomly selected as control, placebo, experimental 1, 2 and 3. The induction of arthritis was carried out by injection of 0.1 ml adjuvant in plantar region. The first experimental group received no curcumin treatment, whereas the experimental two and three received curcumin (1 and 2 g/kg daily) respectively, for fourteen days. MSRA gene expression was assessed by real-time PCR and protein levels of MSRA, SOD, CAT and GPx were analyzed via ELISA method.Results: The results showed no significant weight changes among the groups during the experimental period and the paw swelling caused by adjuvant was recovered within fourteen days of treatment with curcumin. However, the levels of enzymes such as superoxide dismutase, catalase and glutathione peroxidase were increased by a dose dependent manner. These results also illustrated that the gene expression and protein level of MSRA in groups treated with curcumin increased significantly (p≤0.05).Conclusion: We concluded that the curcumin can be used against inflammation. The increasing level of MSRA can be due to the antioxidant effect of curcumin. The enzymatic level changes (MSRA, SOD, CAT and GPx) may interfere with the aging process and delay it.Keywords: curcumin, anti-inflammation, MSRA